THE REPRESENTATION OF SISTERHOOD IN SUSAN GLASPELL'S TRIFLE: PROXEMIC AND KINESIC ANALYSES - Ni Komang Arie Suwastini; Alexei Wahyudiputra (Lakon : Jurnal Kajian Sastra dan Budaya, 2021)
Abstract: Susan Glaspell’s plays have been recognized for its feminist ideologies. The present study traces the representations of the notion of sisterhood in Glaspell’s scrip entitled Trifles by employing Barthes’ semiotics and Fischer-Lichte’s concept of kinesics. Focusing on the gestural and the proxemic signs of the kinesics included in the script, the present study reveals that the notion of sisterhood grows among the female characters in the play through the increasing realization of their similar positions as women in patriarchal society. This development of solidarity among the female characters implies a strong feminist ideology about how women should stand together in facing oppression in male-dominated structures.